Molecular Heterogeneity in Pediatric Malignant Rhabdoid Tumors in Patients With Multi-Organ Involvement - Miller, Katherine E.; Wheeler, Gregory; LaHaye, Stephanie; Schieffer, Kathleen M.; Cearlock, Sydney; Venkata, Lakshmi Prakruthi Rao; Bravo, Alejandro Otero; Grischow, Olivia E.; Kelly, Benjamin J.; White, Peter; Pierson, Christopher R.; Boué, Daniel R.; et al. (Frontiers in Oncology, 2022)
Rhabdoid tumors of the brain (atypical teratoid/rhabdoid tumor; AT/RT) and extracranial sites (most often the kidney; RTK) are malignant tumors predominantly occurring in children, frequently those with SMARCB1 germline alterations. We present data from seven RTs from three pediatric patients who all had multi-organ involvement. Tumors were analyzed using a multimodal approach which included exome sequencing of tumor and germline comparator, RNA-sequencing, and DNA array-based methylation profiling of tumors. SMARCB1 germline alterations were identified in all patients and in all tumors, we observed a second hit in SMARCB1 via chr22 LOH. By methylation profiling, all tumors classified as rhabdoid tumors with corresponding subclassification within the MYC, TYR, or SHH subgroups. Using RNA-seq gene expression clustering, we recapitulated classification of known AT/RT subgroups. Synchronous brain and kidney tumors from the same patient showed different patterns of either copy number variants, single nucleotide variants, and/or genome-wide DNA methylation, suggestive of non-clonal origin. Furthermore, we demonstrated that a lung and abdominal metastasis from two patients shared overlapping molecular features with the patient’s primary kidney tumor, indicating the likely origin of the metastasis. In addition to the SMARCB1 events, we identified other whole-chromosome events and single nucleotide variants in tumors but none were found to be medically meaningful. While our findings are of biological interest, there may also be clinical value in comprehensive molecular profiling in patients with multiple rhabdoid tumors, particularly given the potential prognostic and therapeutic implications for different rhabdoid tumor subgroups demonstrated in recent clinical trials and other large cohort studies.